The responsibility for legal actions made under conditions of lack of consent of the authorized body of the company, that was required a contract or statute - Chrabkowski, Marek (Studia Iuridica Toruniensia, 2020)
In accordance with the law, legal action without the consent of the competent authority of the company, that was required only by the provisions of company statute or company agreement, is important, however, this does not exclude the liability of the members of the management board against the company for breach of company statute or the articles of association. This article presents the results of research, whose purpose was to determine the scope of recipients for this provision, as well as the issue of avoidance of liability by the people, which, although they made efficiently a legal transaction, they received the post factum consent from the competent authority the company. Studies have been carried out with the use of research methods used in legal sciences.